Studying the Physics of Vertical Transfer of Emissions from Industrial Enterprises in the Surface Layer of the Atmosphere; Russian Physics Journal; Vol. 65, iss. 4 - Ryzhakova (Rizhakova) N. K. Nadezhda Kirillovna; Rogova N. S. Natalya Sergeevna; Pokrovskaya E. A. Elena Aleksandrovna; Taylasheva K. A. Kseniya Alekseevna; Borisenko A. L. Aleksey Lvovich (2022, 2022)
Title screen